Pemanfaatan Media Sosial Sebagai Sarana Promosi Layanan Perpustakaan Institut Seni Indonesia Surakarta - M. Ali Nurhasan Islamy; Ika Laksmiwati (Nusantara Journal of Information and Library Studies (N-JILS), 2020)
This study is entitled Utilization of Social Media as a Means of Promoting Library Services in Indonesia Institute of the Arts Surakarta. The purpose of this research is to find out whether social media (Facebook) can provide convenience in introducing various services, providingan an information to users in the current style. In addition, to find out whether facebook can be used to effectively promoting an information services and activities in the library. Researchers will look at facebook, collect documentation data on facebook library pages and analyze them using descriptive qualitative analysis. The approach used is a qualitative approach, namely research that describes the phenomenon, digging data by interviewing informants, observation and documentation. Researchers' technique in finding data will be done directly through online media or the internet by structured interviews and checklists. It's just that if needed the researcher will meet directly the informant. Researchers assume that social media can be used as a substitute for the promotion of library services in the form of online or softcopy and simultaneously to many people and quickly and sometimes even immediately get a response or public response. In addition, promotion with social media can attract users to take of library facilities and participate in library activities and as a media for documentation of various activities in the library. The results of this research are expected to be input and thought for the Library of  Indonesian Institute of Arts Surakarta, namely how to promote library services through facebook in this modern era so that the academic community utilizes services library.